TRANSFORMASI ARKEOLOGI PERAHU KUNO DI PESISIR PANTAI TIMUR SUMATERA - Stanov Purnawibowo (Berkala Arkeologi Sangkhakala, 2006)
The transformation process of archaeological data which foundon “sampan sudur” artifact in Terjun River and Padang River isthe Natural Transformation. It is said that the “sampan sudur” isnot in use now by its material cultural support.